FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUASAN WISATAWAN TERHADAP PRODUK FREESTANDING RESTAURANT DI KAWASAN PARIWISATA NUSA DUA – KABUPATEN BADUNG - Suastuti, Ni Luh (Jurnal Ilmiah Pariwisata, 2012)
Tourist satisfaction is an accomplishment of tourist expectation. It needs long process, time and is often expensive. In service industries especially food and beverage services, customer satisfaction becomes success parameter. The researcher took five factors of restaurant’s product, foods and beverages through four variables, service  through seven variables, cleanliness and hygiene through three variables, price through three variables, and atmosphere through five variables. This research was done in freestanding restaurants in Nusa Dua Tourism Area that are located in Bali Collection inside BTDC area, on Pantai Mengiat Street and Main Gate BTDC outside of BTDC Area. In this research, there were 110 respondents selected as a sample using purposive sampling method. Data was collected by using questioners spreaded to the tourists who were trying the product in freestanding restaurants. Data analyzed by confirmatory factor analysis and determinant analysis with SPSS program version 19.0. The research findings are: a) the level of tourists satisfaction toward freestanding restaurants’ product in Nusa Dua Tourism Area  is generally  satisfied enough, b) The five factors in this research have their own influence towards tourists satisfaction on freestanding restaurants’ product, but the factor which has the strongest influence is service factor, and the smallest influence is price factor, and c) there are the differences between tourist who try the product inside BTDC and outside BTDC and tourist group inside BTDC are more satisfied than the outside ones.
Keywords: tourist satisfaction, services, freestanding restaurant